(untitled) (Psychology Travelogs, 2023)
The article presents an analysis of psychological and pedagogical research on the problem of forming additive behavior in modern youth and its impact on the social, moral, physical and psychological spheres of the individual. The content of the concept of addiction as a desire to rely on someone or something for the purpose of obtaining pleasure or adaptation, dependence on certain objects, substances or types of activities is highlighted. The concept of addictive behavior is considered, which is one of the forms of deviant behavior and is interpreted as one of the forms of deviant behavior, destructive behavior, with the formation of a desire to depart from reality by artificially changing one’s mental state due to the use of various chemical substances or constant fixation of attention on certain types of activities in order to develop and maintain intense emotions. The types of addiction are analyzed: psychological and physical. Psychological addiction can be considered as a constant, obsessive need to change one’s state with the help of a certain object and experiencing emotional discomfort in its absence. Physical dependence arises in an individual as a result of the use of psychotropic chemicals and manifests itself in a state of physical discomfort when it is not present in the body (withdrawal syndrome). The factors of addictive behavior, the factors that determine it, as well as its motivational determinants are highlighted. Among the factors of additive behavior, the following are distinguished: moral immaturity of the individual, disturbed social microenvironment, individual-biological features, individual-psychological and neuropsychological anomalies of the individual. Models of prevention of addictive behavior among modern youth are presented: informational and behavioral. According to the information model, knowledge of the negative consequences of bad habits deters them. The legal aspect involves informing about the legal consequences of drug use and distribution, crimes committed while under the influence of drugs or alcohol.